One IV HEDGES DNA vector administration encoding hGLA or hGH produces durable hGLA and hGH serum lvels in immunocompetent mice - Alice Ye; Marissa Mack; Sarah Ursu; Stephen Chmura; Robert Steiner; Tim Heath; Chakkrapong Handumrongkul; Robert Debs (PLoS ONE, 2025)
The great majority of human monogenic, single protein deficiency disease patients, who comprise ~ 0.5% of the population, are incurable. When available, Enzyme Replacement Therapy (ERT) is current state-of-the art therapy for the vast majority of the subset of these diseases caused by enzyme deficiencies. For example, Fabry disease, caused by hemizygous- or heterozygous-pathogenic variants in GLA encoding human-galactocersbrosidase-α (hGLA), is a rare, single protein-deficiency disease. Fabry patients require intravenous-administration of hGLA Enzyme Replacement Therapy (ERT) every two-weeks for-life. ERT costs ~ $300,000 per-year and can cause frequent infusion reactions, which can be life-threatening. The very-high yearly GLA ERT costs, as well as the recurrent, life-threatening hGLA IV infusion-reactions experienced by some patients, can cause them to permanently-discontinue ERT. This can accelerate Fabry-disease progression, leading to premature-death. Therefore, new, more effective-, safe-, durable-, cost-effective, single deficient-protein replacement platforms are urgently-needed to more-effectively treat a wide-spectrum of these rare, monogenic single protein deficiency diseases. Here we demonstrate that one intravenous-administration of our 1 st -generation HEDGES DNA-vector encoding wildtype-hGLA (T 1 / 2 < 20-minutes) produced hGLA serum-protein levels in the normal human 1,000-10,000 pg/ml range for only < 14 days. We then-created our 2 nd -generation HEDGES hGLA DNA-vector. One intravenous-administration of this DNA-vector produced durable (>550 days) serum hGLA serum levels in the 1–10 ng/ml, thus increasing the duration of hGLA serum-protein levels produced by > 38,100 fold versus administering bioreactor-produced, wildtype hGLA-protein. We also showed one intravenous-administration of our 1 st -generation HEDGES DNA-vector encoding the wildtype human growth hormone (hGH) protein, (T 1 / 2 < 20-minutes), produced serum hGH levels in the 1–10 ng/ml for > 330 days, thus increasing the duration of hGLA serum-protein levels by > 22,860 fold versus administering wildtype hGH-protein. Last, one intravenous-administration of our 2 nd -generation HEDGES hGLA DNA-vector produced serum hGLA levels in the normal human 1–10 ng/ml range for > 160 days in GLA knockout-mice, a 2,800-fold increase versus wildtype hGLA-protein. hGLA-ERT produces major therapeutic-responses in GLA knockout-mice. These substantial ERT-responses in GLA knockout-mice have been shown to be accurately-recapitulated in Fabry patients. Thus, Fabry disease appears a promising-target for subsequent phase-1 HEDGES-based human clinical trials.